Deficiency of miR-29a/b1 leads to premature aging and dopaminergic neuroprotection in mice - Bai, Xiaochen; Wang, Jinghui; Zhang, Xiaoshuang; Tang, Yilin; He, Yongtao; Zhao, Jiayin; Han, Linlin; Fang, Rong; Liu, Zhaolin; Dong, Hongtian; Li, Qing; Ge, Jingyu; et al. (Frontiers in Molecular Neuroscience, 2022)
Parkinson’s disease (PD) is a neurodegenerative disorder characterized by progressive degeneration of midbrain dopaminergic neurons. The miR-29s family, including miR-29a and miR-29b1 as well as miR-29b2 and miR-29c, are implicated in aging, metabolism, neuronal survival, and neurological disorders. In this study, the roles of miR-29a/b1 in aging and PD were investigated. miR-29a/b1 knockout mice (named as 29a KO hereafter) and their wild-type (WT) controls were used to analyze aging-related phenotypes. After challenged with the neurotoxin MPTP, dopaminergic injuries, glial activation and mouse behaviors were evaluated. Primary glial cells were further cultured to explore the underlying mechanisms. Additionally, the levels of miR-29s in the cerebrospinal fluid (CSF) of PD patients (n=18) and healthy subjects (n=17) were quantified. 29a KO mice showed dramatic weight loss, kyphosis, along with increased and deepened wrinkles in skins, when compared with wild-type (WT) mice. Moreover, both abdominal and brown adipose tissues reduced in 29a KO mice, compared to their WT counterpart. However, in MPTP-induced PD mouse model, deficiency of miR-29a/b1 led to less severe damages of dopaminergic system and mitigated glial activation in the nigrostriatal pathway, and subsequently alleviated the motor impairment in 3-month-old mice. 8-month-old mutant mice maintained such a resistance to MPTP intoxication. Mechanistically, the deficiency of miR-29a/b-1 promoted the expression of neurotrophic factors in MPP+-treated primary mixed glia and primary astrocytes. In LPS-treated primary microglia, knockout of miR-29a/b-1 inhibited the expression of inflammatory factors, and promoted the expression of anti-inflammatory factors and neurotrophic factors. Knockout of miR-29a/b1 gene increased the activity of AMPK and repressed NF-κB/p65 signaling in glial cells. Moreover, we found miR-29a level was increased in the CSF of patients with PD. Our results suggest that 29a KO mice display the peripheral premature senility. The combined effects of less activated glial cells might contribute to the mitigated inflammatory responses and elicit resistance to MPTP intoxication in miR-29a/b1 KO mice.